Kultúrne dedičstvo a globalne / lokalne prejavy v súčasnom malom meste - Koštialová, Katarína (Studia Etnologiczne i Antropologiczne, 2014)
This paper considers the cultural heritage and global / local manifestation in urban spaces. It focuses on cultural monuments, phenomena, events and the image of the city, which form a historical continuum and the part of today's city culture with the overlap between global and local elements, forms and functions. Global and local manifestations enable compliance or conflict that may promote, encourage, even out or damage cultural heritage. Municipal institutions, NGOs, individuals and foreign investors and entrepreneurs enter into this process. The paper is the result of field research in Zvolen located in central Slovakia.